Factibilidad económica de los programas de intervención ergonómica de los factores psicosociales, condiciones y organización del trabajo, área de Pecuaria, Espam-MFL - Bravo Bravo, Francisco Rigoberto (2015)
The economic study feasibility of the ergonomic intervention programs of the psychosocial factors, conditions and organization of the job were analyzed in the Units of Teaching, Social Outreach and Research (U.T.S.R.) of the Animal Science area in the ESPAM MFL, a bibliographic research of various sources generated comprehensive knowledge of the variables in study. For the execution of this investigation the procedure of Félix (2014) was considered and adopted by Quevedo (2014), from which two development periods came true; the first one described the present situation of the U.T.S.R. for which, it was necessary to accomplish several activities like the application of the checklist and poll that helped to identify the problems of workers and coordinators in the job positions focused on psychosocial factors, conditions and organization. The second stage set an improving plan for the application of preventive and corrective measures, besides an investment plan that overtook an amount of $5.328,00. Finally, the results were socialized to the staff of labors different units of the area of animal science, showing the benefits that they would obtain with the application of the measured being proposed as guide to the well-being of the workers.